Prognostic value of lymphovascular invasion in Bismuth-Corlette type IV hilar cholangiocarcinoma - Li, Bei (World J Gastroenterol, 2017)
AIM: To assess the prognostic value of lymphovascular invasion (LVI) in Bismuth-Corlette type IV hilar cholangiocarcinoma (HC) patients. METHODS: A retrospective analysis was performed on 142 consecutively recruited type IV HC patients undergoing radical resection with at least 5 years of follow-up. Survival analysis was performed by the Kaplan-Meier method, and the association between the clinicopathologic variables and survival was evaluated by log-rank test. Multivariate analysis was adopted to identify the independent prognostic factors for overall survival (OS) and disease-free survival (DFS). Multiple logistic regression analysis was performed to determine the association between LVI and potential variables. RESULTS: LVI was confirmed histopathologically in 29 (20.4%) patients. Multivariate analysis showed that positive resection margin (HR = 6.255, 95%CI: 3.485-11.229, P < 0.001), N1 stage (HR = 2.902, 95%CI: 1.132-7.439, P = 0.027), tumor size > 30 mm (HR = 1.942, 95%CI: 1.176-3.209, P = 0.010) and LVI positivity (HR = 2.799, 95%CI: 1.588-4.935, P < 0.001) were adverse prognostic factors for DFS. The independent risk factors for OS were positive resection margin (HR = 6.776, 95%CI: 3.988-11.479, P < 0.001), N1 stage (HR = 2.827, 95%CI: 1.243-6.429, P = 0.013), tumor size > 30 mm (HR = 1.739, 95%CI: 1.101-2.745, P = 0.018) and LVI positivity (HR = 2.908, 95%CI: 1.712-4.938, P < 0.001). LVI was associated with N1 stage and tumor size > 30 mm. Multiple logistic regression analysis indicated that N1 stage (HR = 3.312, 95%CI: 1.338-8.198, P = 0.026) and tumor size > 30 mm (HR = 3.258, 95%CI: 1.288-8.236, P = 0.013) were associated with LVI. CONCLUSION: LVI is associated with N1 stage and tumor size > 30 mm and adversely influences DFS and OS in type IV HC patients.